Sercob Application Design: IT Consultant in Overcoming Computer Problems in The Digital 4.0 Era - Bakti Dwi Waluyo; Rivaldo Effendi; Andreas Pratama Partogu Hutabarat; Angga Koswara Malau; Deskristina Siregar; Dita Febiyan Pratiwi (Institute of Computer Science (IOCS), 2021)
The use of computers in the digital era 4.0 is increasing rapidly; with the increasing use of computers, the problems experienced by computer users are also increasing. With the problems encountered by computer users, a computer service center is needed to solve computer user problems. SERCOB-IT functions as a platform that provides technicians and service points according to the location of computer users who experience computer problems. SERCOB-IT is a website-based application with an order-taking function and learning media related to laptop maintenance and information about laptops. Through the Independent Learning Activity Program for Merdeka Edupreneur Campus, the SERCOB-IT application has been launched and advertised through several offline and online social media. Therefore, it has the opportunity to become a new digital-based company.